Achievement and Attitude of Students and Teachers Towards B.Ed. Course: Enhancing the Quality of B.Ed. Education (Journal of Advances and Scholarly Researches in Allied Education, 2014)
To ensure quality teachers are churned out of trainingcolleges, the National Council for Teacher Education (NCTE) is making somesweeping changes from the next academic year. It is increasing the duration ofthe Bachelor of Education (B.Ed.) programme from one year to two years, besidesmodifying the curriculum. This means now one has to study for five years to becomea teacher, as the minimum eligibility to pursue B.Ed. is a three-yearundergraduate programme. Experts feel the change will lend the programme thegravitas enjoyed by other professional courses like BE (four years) and MBBS(five-and-a-half years). P Revathi Reddy, regional director of NCTE, told TOI thatsyllabus for B.Ed. will also be changed. A framework to formulate the syllabuswill be sent to all universities. The aim is to produce quality teachers, shesaid, adding that all colleges and universities across the country offeringB.Ed. must follow the new norms. Now, the question arises “Is it wise for thenation to part with the funds allocated for pre-school and elementaryeducation?” The paper gives some more suggestions for improving the quality.